A study of leachate treatment by anaerobic baffled reactor (abr) - Nguyen, Văn Sức; Nguyen, Duy Đạt (Journal of Technical Education Science, 2011)
This paper presents the results of studied activities of the anaerobic baffled reactor (ABR) to treat the leachate at the laboratory scale. Results showed that activity of ABR can withstand the shock of COD loading. The biological constants were determined such as the endogenous decay rate(kd) and the cell yield coefficient (Y). Principal component analysis (PCA) by SYSTAT 13 software showed a close relation between variables of pH, alkalinity, VSS and COD in the performance of ABR